Liberalization of trade in services and diversification of CARICOM exports - Freckleton, Marie (2000)
Examines the prospects for expansion and diversification of CARICOM's exports in the context of global liberalization of trade in services. Argues that significant policy changes will have to be implemented in order to position CARICOM countries to exploit the emerging trade opportunities in services.